Melanocyte abnormalities and senescence in the pathogenesis of idiopathic guttate hypomelanosis. (8th March 2018) - Rani, Seema; Kumar, Ravinder; Kumarasinghe, Prasad; Bhardwaj, Supriya; Srivastava, Niharika; Madaan, Aaisha; Parsad, Davinder
Abstract: Background: Idiopathic guttate hypomelanosis (IGH) is a pigmentary disorder of unknown pathogenesis characterized by small discrete white macules. In the skin, epidermal melanin unit between melanocytes and keratinocytes is responsible for melanin synthesis and equal distribution of melanin pigment. Objective: Therefore, this study was designed to check the role of melanocytes in the pathogenesis of IGH. Methods: For this study, six IGH patients and six controls were enrolled. Melanin content was checked in the skin sections and in the cultured melanocytes. Senescence was checked in the lesional skin of IGH patients by comparing the mRNA and protein expression of senescence markers p16, hp1, and p21 . Results: Cultured melanocytes from the IGH patients showed morphological changes in comparison to the control melanocytes. Melanocytes from IGH patients were bigger in size with very small and retracted dendrites as compared to the control melanocytes. Melanin accumulation was more in the IGH patients as compared to the controls. Our results showed that expression of p16, p21, and hp1 was significantly higher in lesional skin of IGH patient as compared to healthy controls. Conclusion: This study revealed large‐sized melanocytes with small and retracted dendrites in IGH patients. Accumulation of more melanin in the IGH melanocytes might be due to problem in the transfer of melanin from melanocytes to keratinocytes. Accumulation of melanin can lead to the senescence in the melanocytes of IGH patients.